Las narrativas visuales como herramienta de aprendizaje para preservar las leyendas tradicionales del Ecuador, en niños de quinto año de educación básica - Robalino Riofrio, Ricardo Xavier (2024)
The project in question focuses on the use of visual narratives as a learning tool to preserve and revalue traditional legends of Ecuador, specifically targeting fifth-grade students in basic education. The research integrates bibliographic and field elements. Information gathering is conducted through interviews with experts in education, culture, and designers specialized in the layout of pop-up books. Additionally, observation sheets are applied to children to identify appropriate graphic styles, fonts, and formats, thus customizing the product for the target audience. The culminating result of this work is the creation of a concrete proposal: the design of an interactive book with pop-up mechanisms. This innovative initiative provides visual support to textual narrative, significantly enhancing children's attention and increasing information saliency. The intersection of education, culture, and graphic design materializes in this proposal, offering a practical and engaging approach to transmitting traditional legends. This project aspires not only to enrich the educational experience of children but also to actively revitalize and preserve Ecuador's rich cultural heritage through visually captivating and pedagogically effective means. With the aim of enhancing understanding and interest in traditional legends, this project seeks to contribute to the development of visual and cognitive skills in children, thus fostering the transmission of cultural knowledge and the promotion of diversity in society